Identifying target ion channel-related genes to construct a diagnosis model for insulinoma - Mo, Shuangyang; Wang, Yingwei; Wu, Wenhong; Zhao, Huaying; Jiang, Haixing; Qin, Shanyu (Frontiers in Genetics, 2023)
Background: Insulinoma is the most common functional pancreatic neuroendocrine tumor (PNET) with abnormal insulin hypersecretion. The etiopathogenesis of insulinomas remains indefinable. Based on multiple bioinformatics methods and machine learning algorithms, this study proposed exploring the molecular mechanism from ion channel-related genes to establish a genetic diagnosis model for insulinomas.The mRNA expression profile dataset of GSE73338 was applied to the analysis, which contains 17 insulinoma samples, 63 nonfunctional PNET (NFPNET) samples, and 4 normal islet samples. Differently expressed ion channel-related genes (DEICRGs) enrichment analyses were performed. We utilized the protein-protein interaction (PPI) analysis and machine learning of lasso and support vector machinesrecursive feature elimination (SVM-RFE) to identify the target genes. Based on the target genes, a nomogram diagnostic model was constructed and verified by a receiver operating characteristic (ROC) curve. Moreover, immune infiltration analysis, singlegene gene set enrichment analysis (GESA), and gene set variation analysis (GSVA) were executed. Finally, a drug-gene interaction network was constructed.We identified 29 DEICRGs, and enrichment analyses indicated they were primarily enriched in ion transport, cellular ion homeostasis, pancreatic secretion, and lysosome. Moreover, the PPI network and machine learning recognized three target genes (MCOLN1, ATP6V0E1, and ATP4A). Based on these target genes, we constructed an efficiently predictable diagnosis model for identifying insulinomas with a nomogram and validated it with the ROC curve (AUC=0.801, 95%CI 0.674 -0.898).Then single-gene GESA analysis revealed that these target genes had a significantly positive correlation with insulin secretion and lysosome. In contrast, the TGF−beta signaling pathway was negatively associated with them. Furthermore, statistically significant discrepancies in immune infiltration were revealed.We identified three ion channel-related genes and constructed an efficiently predictable diagnosis model to offer a novel approach for diagnosing insulinomas.